Diets shape thermal responses in Chinese giant salamanders by altering liver metabolism - Zhai, Runliang; Zhao, Chunlin; Chang, Liming; Liu, Jiongyu; Zhao, Tian; Jiang, Jianping; Zhu, Wei (Frontiers in Microbiology, 2025)
Diet can influence the thermal performance of ectotherms, providing potential strategies for biological conservation in the context of global warming. The endangered Andrias davidianus is susceptible to heat stress due to energy deficiency in the liver when fed a worm-based diet rich in carbohydrates. A fish-based diet, rich in protein and lipids, improves their thermal performance, but the underlying physiological mechanisms remain unclear. In this study, we used metabolomics and metagenomics to examine the combined effects of temperature (15, 20, and 25°C) and diet (fish-based and worm-based) on liver metabolism and gut microbiota. Our results show that both temperature and diet shape liver metabolism, with several vital metabolic pathways (e.g., TCA cycle and sulfate metabolism) regulated by their combined effects. Notably, diet-dependent thermal responses in energy metabolism were observed, with fish-fed salamanders exhibiting a marked upregulation of the TCA cycle intermediates under heat stress, a response absent in worm-fed individuals. Given the role of TCA cycle in heat susceptibility of A. davidianus, these findings suggest that the TCA cycle likely mediates the interactive effects of temperature and diet on thermal performance. We then examined whether the gut microbiota is also a target of interactive effects or a mediator of the diet’s influence on liver metabolism. While both temperature and diet shape microbiota composition, functional shifts occur only in response to temperature, indicating that the microbiota is not a major link between diet and liver metabolism. However, several bacterial groups (e.g., Thiosulfatimonas and Alcanivorax), jointly regulated by temperature and diet, correlate with liver metabolites, suggesting alternative, function-independent pathways through which dietary-related microbial changes may influence liver metabolism and even thermal tolerance. Overall, this study provides molecular insights into the dietary modulation of thermal performance in A. davidianus and highlight the potential of dietary microbial management strategies for amphibian conservation.